2018
DOI: 10.1007/s11663-018-1446-x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Physical and Numerical Approaches for the Study of Gas Stirring in Ladle Metallurgy

Abstract: This article presents a review of the research into gas stirring in ladle metallurgy carried out over the past few decades. Herein, the physical modeling experiments are divided into four major areas: (1) mixing and homogenization in the ladle; (2) gas bubble formation, transformation, and interactions in the plume zone; (3) inclusion behavior at the steel-slag interface and in the molten steel; and (4) open eye formation. Several industrial trials have also been carried out to optimize gas stirring and open e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 126 publications
(243 reference statements)
0
54
0
Order By: Relevance
“…Accordingly, there has been a great interest to understand the effect of different process parameters on the mixing time in ladles, [2][3][4] including the gas flow rate, the number of plugs, the radial and angular position of the plugs in systems with multiple gas injection points, the presence or absence of slag, the thickness of the slag layer, and the diameter of the plugs, among other variables. The gas flow rate is by far the variable affecting the most the mixing time and it is well known that the larger the gas flow rate the shorter is the mixing time obtained in ladles.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there has been a great interest to understand the effect of different process parameters on the mixing time in ladles, [2][3][4] including the gas flow rate, the number of plugs, the radial and angular position of the plugs in systems with multiple gas injection points, the presence or absence of slag, the thickness of the slag layer, and the diameter of the plugs, among other variables. The gas flow rate is by far the variable affecting the most the mixing time and it is well known that the larger the gas flow rate the shorter is the mixing time obtained in ladles.…”
Section: Introductionmentioning
confidence: 99%
“…For the ±5% homogenization degree case, the mixing time was determined as the concentration of the tracer, which was continuously within ±5% of a well-mixed bulk value. [2] The procedure was the same for the case of a ±1% homogenization degree case, but the mixing time corresponded to a ±1% well-mixed bulk value. The configurations of porous plugs and conductivity probes in the mixing experiment are shown in Figure 5.…”
Section: Gas Bubbling and Mixing Conditions In The Physical Modellingmentioning
confidence: 99%
“…The solid and dashed lines represent the tracer concentration within ±5% and ±1% of the homogenization degrees' value, respectively. For the ±5% homogenization degree case, the mixing time was determined as the concentration of the tracer, which was continuously within ±5% of a well-mixed bulk value [2]. The procedure was the same for the case of a ±1% homogenization degree case, but the mixing time corresponded to a ±1% well-mixed bulk value.…”
Section: Gas Bubbling and Mixing Conditions In The Physical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that this limitation is however compensated by a low dependency of heat and mass transfer rates on turbulence inside the ladle. Detailed reviews of modeling-based simulation studies in ladles can be found in [2][3][4].…”
Section: Introductionmentioning
confidence: 99%